2023
DOI: 10.3390/tropicalmed8020097
|View full text |Cite
|
Sign up to set email alerts
|

Basic Aspects and Epidemiological Studies on Leptospirosis Carried Out in Animals in Chile: A Bibliographic Review

Abstract: Leptospirosis is an important zoonosis worldwide. This disease affects numerous animal species, some of them are classified as “maintenance hosts”, and others are categorized as “incidental hosts”. Humans are at risk of becoming infected by having contact with domestic and wild animals. In this paper, general aspects of the etiology and transmission of leptospirosis are addressed, data regarding the clinical presentation of the pathology in humans and animals are also presented, and the results of some epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 68 publications
0
12
0
3
Order By: Relevance
“…In relation to the serogroup distribution, even though only half of the sequences had that information, strains of Icterohaemorrhagiae were by far the major agent of canine infection. In contrast, many serosurveys studies carried out in Latin America frequently reported the presence of strains of Canicola, Autumnalis, and Pomona besides Icterohaemorrhagiae [29,[35][36][37][38], and their real role in canine leptospirosis remains to be elucidated. On the other hand, the number of sequences recognized as the Canicola serogroup was surprisingly low since dogs are known to be the maintenance host of this serogroup [10].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In relation to the serogroup distribution, even though only half of the sequences had that information, strains of Icterohaemorrhagiae were by far the major agent of canine infection. In contrast, many serosurveys studies carried out in Latin America frequently reported the presence of strains of Canicola, Autumnalis, and Pomona besides Icterohaemorrhagiae [29,[35][36][37][38], and their real role in canine leptospirosis remains to be elucidated. On the other hand, the number of sequences recognized as the Canicola serogroup was surprisingly low since dogs are known to be the maintenance host of this serogroup [10].…”
Section: Discussionmentioning
confidence: 91%
“…A serosurvey in Colombia found Autumnalis and Canicola as the most prevalent serovars [35]. Still, seroprevalence studies in Chile reported the presence of Canicola, Pomona, and Autumnalis in both urban and rural areas [36,37]. Isolates were recovered from urine (n = 6), blood (n = 1), and fetus (n = 1) in Argentina.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, more research is needed to determine the role of wild animals in the epidemiology of leptospirosis [14]. According to a recent study in Chile, their prevalence is between 12.0% and 59.1%, between 3.0% and 25.2%, and between 23.3% and 65.4% in domestic animals such as dogs, domestic felines, and horses, respectively [39].…”
Section: Discussionmentioning
confidence: 99%
“…Most published studies on small and large ruminant renal diseases have used serological, culture, pathological, and molecular diagnostic techniques, either separately or in combination, to assess the presence of Leptospira spp. [ 29 , 30 ]. Few reports have described the use of histopathological, culture, serological, and PCR tests to assess renal diseases.…”
Section: Discussionmentioning
confidence: 99%